2007
DOI: 10.1016/j.neuron.2007.07.038
|View full text |Cite
|
Sign up to set email alerts
|

EphA4-Dependent Axon Guidance Is Mediated by the RacGAP α2-Chimaerin

Abstract: Neuronal network formation in the developing nervous system is dependent on the accurate navigation of nerve cell axons and dendrites, which is controlled by attractive and repulsive guidance cues. Ephrins and their cognate Eph receptors mediate many repulsive axonal guidance decisions by intercellular interactions resulting in growth cone collapse and axon retraction of the Eph-presenting neuron. We show that the Rac-specific GTPase-activating protein alpha2-chimaerin binds activated EphA4 and mediates EphA4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
118
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 47 publications
7
118
1
3
Order By: Relevance
“…The novel EphA4 -SPAR-Rap1 pathway that we have identified likely acts in concert with other Ras and Rho pathways that are also activated downstream of EphA receptors to sculpt neuronal morphology and control the establishment and remodeling of neuronal connections Sahin et al, 2005;Beg et al, 2007;Fu et al, 2007a;Iwasato et al, 2007;Wegmeyer et al, 2007). Because SPAR is a ubiquitously expressed protein and part of a family of three related proteins, the Eph-SPAR signaling connection may operate widely to regulate adhesion and morphology of many cell types through control over the different activities of Rap1 and Rap2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel EphA4 -SPAR-Rap1 pathway that we have identified likely acts in concert with other Ras and Rho pathways that are also activated downstream of EphA receptors to sculpt neuronal morphology and control the establishment and remodeling of neuronal connections Sahin et al, 2005;Beg et al, 2007;Fu et al, 2007a;Iwasato et al, 2007;Wegmeyer et al, 2007). Because SPAR is a ubiquitously expressed protein and part of a family of three related proteins, the Eph-SPAR signaling connection may operate widely to regulate adhesion and morphology of many cell types through control over the different activities of Rap1 and Rap2.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, GTPase-activating proteins (GAPs) accelerate the hydrolysis of GTP to GDP. ␣2-Chimaerin, a GTPase-activating protein for Rac, and p120RasGAP, a GTPase-activating protein for H-Ras and R-Ras, have been recently implicated in EphA-dependent repulsive responses (Dail et al, 2006;Beg et al, 2007;Iwasato et al, 2007;Wegmeyer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the C1 domain is important for the subcellular localization of some of these family members [34,35]. The α2-and β2-family members have also an N-terminal SH2 domain involved, presumably, in heteromolecular interactions [31,[36][37][38]. α2-chimerin has been the focus of recent attention because the it has been found that the spontaneous mouse mutation miffy maps within the chn1 locus [39].…”
Section: Introductionmentioning
confidence: 99%
“…α2-chimerin has been the focus of recent attention because the it has been found that the spontaneous mouse mutation miffy maps within the chn1 locus [39]. This mutation, which is reproduced by the knockout of the chn1 gene [38][39][40], induces locomotor problems due to corticospinal axon guidance defects. We hypothesized that the function of chimaerin family members could also extended to the downmodulation of TCR signaling since these GAPs are regulated by DAG [28,41], an intracellular second messenger that plays pleiotropic roles during T-cell signaling [1].…”
Section: Introductionmentioning
confidence: 99%
“…The functions of chimaerins in the nervous system are just beginning to be understood [13-18]. Recently convergent evidence from three laboratories [14-16] implicated α2-chimaerin as an essential mediator of ephrinB3/EphA4-dependent motor circuit formation. Mutations of ephrinB3, EphA4 or α2-chimaerin produce a characteristic hopping rabbit like gait.…”
Section: Discussionmentioning
confidence: 99%